Current state of, prospects for, and obstacles to mRNA vaccine development. Issue 2 (February 2023) - Aljabali, Alaa A.A.; Bashatwah, Rasha M.; Obeid, Mohammad A.; Mishra, Vijay; Mishra, Yachana; Serrano-Aroca, Ángel; Lundstrom, Kenneth; Tambuwala, Murtaza M.
Graphical abstract: Highlights: mRNA is a key component of mRNA vaccine as the biological blueprint encoding for proteins. mRNA strategies comprise preventive vaccinations for therapeutic vaccines, and protein-encoding treatments. mRNA vaccine production is cheap, rapid, effective and safe. mRNA therapy combines the benefits of gene and protein therapy. Abstract : Given their superior efficacy, rapid engineering, low-cost manufacturing, and safe delivery prospects, mRNA vaccines offer an intriguing alternative to conventional vaccination technologies. Several mRNA vaccine platforms targeting infectious diseases and various types of cancer have exhibited beneficial results both in vivo and in vitro . Issues related to mRNA stability and immunogenicity have been addressed. Current mRNA vaccines can generate robust immune responses, without being constrained by the major histocompatibility complex (MHC) haplotype of the recipient. Given that mRNA vaccinations are the only transient genetic information carriers, they are also safe. In this review, we provide an update and overview on mRNA vaccines, including their current state, and the problems that have prevented them from being used in more general therapeutic ways.